(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
The article highlights the relevance of the fight against corruption, data from international organizations on customs problems, threats of corruption at customs, the importance of information and analytical activities, positive results of the use of information and analytical activities in the fight against corruption.